Exercise Testing, Physical Training and Fatigue in Patients with Mitochondrial Myopathy Related to mtDNA Mutations - Jeppesen, Tina D. (J Clin Med, 2021)
Mutations in mitochondrial DNA (mtDNA) cause disruption of the oxidative phosphorylation chain and impair energy production in cells throughout the human body. Primary mitochondrial disorders due to mtDNA mutations can present with symptoms from adult-onset mono-organ affection to death in infancy due to multi-organ involvement. The heterogeneous phenotypes that patients with a mutation of mtDNA can present with are thought, at least to some extent, to be a result of differences in mtDNA mutation load among patients and even among tissues in the individual. The most common symptom in patients with mitochondrial myopathy (MM) is exercise intolerance. Since mitochondrial function can be assessed directly in skeletal muscle, exercise studies can be used to elucidate the physiological consequences of defective mitochondria due to mtDNA mutations. Moreover, exercise tests have been developed for diagnostic purposes for mitochondrial myopathy. In this review, we present the rationale for exercise testing of patients with MM due to mutations in mtDNA, evaluate the diagnostic yield of exercise tests for MM and touch upon how exercise tests can be used as tools for follow-up to assess disease course or effects of treatment interventions.